THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND SUCCESS OF EXCLUSIVE BREAST MILK IN INFANTS AGED 6-12 MONTHS IN THE WORKING AREA OF PUSKESMAS SEWON II YOGYAKARTA - Apriza Dwi Yanhari; Yulinda Kurniasari; Anafrin Yugistyowati (Ikatan Sarjana Gizi Indonesia (ISAGI), 2023)
Breast milk (ASI) is the main natural and best food for babies, because it contains nutrients with a composition that suits the baby’s needs and optimal growth and development and protects from various diseases. Exclusive breastfeeding in Indonesia is still low due to family factors that do not support exclusive breastfeeding. Family support is needed by breastfeeding mothers because mothers need attention, affection, support and health information about exclusive breastfeeding from the closest person, namely husband or family. Family support is provided in several forms, namely emotional support, informational support, instrumental support and appraisal support. This study aims to determine relationship between family support and success of exclusive breastfeeding in infants aged 6-12 months in work area of the sewon II health center. The method used observational type with cross sectional approach design, the number of respondents 163 who had infants aged 6-12 months met the inclusion and exclusion criteria. Total sampling techniques and bivariate data analysis using statistical test and Chi-Square test. The results of the analysis showed that family support with the success of exclusive breastfeeding was mostly good at 89.6% and the success of exclusive breastfeeding at 65.6%. There was a significant relationship between family support and the success of exclusive breastfeeding with significant value (p = 0,025<0,05).